2006
DOI: 10.1007/s00441-006-0197-1
|View full text |Cite
|
Sign up to set email alerts
|

Innervation pattern of suboesophageal ventral unpaired median neurones in the honeybee brain

Abstract: In honeybees (Apis mellifera), the biogenic amine octopamine has been shown to play a role in associative and non-associative learning and in the division of labour in the hive. Immunohistochemical studies indicate that the ventral unpaired median (VUM) neurones in the suboesophageal ganglion (SOG) are putatively octopaminergic and therefore might be involved in the octopaminergic modulation of behaviour. In contrast to our knowledge about the behavioural effects of octopamine, only one neurone (VUMmx1) has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 79 publications
(103 reference statements)
4
81
0
Order By: Relevance
“…The higher distances between odour-evoked glomerular response patterns in the right AL might reflect a left-right difference in the interglomerular network. In honey bees, glomeruli are interconnected by a dense network of extrinsic neurons [35][36][37][38][39] and local interneurons [19,40], many of which are inhibitory [41]. The strength of inter-glomerular inhibitory connections is variable within and across ALs [42].…”
Section: Discussionmentioning
confidence: 99%
“…The higher distances between odour-evoked glomerular response patterns in the right AL might reflect a left-right difference in the interglomerular network. In honey bees, glomeruli are interconnected by a dense network of extrinsic neurons [35][36][37][38][39] and local interneurons [19,40], many of which are inhibitory [41]. The strength of inter-glomerular inhibitory connections is variable within and across ALs [42].…”
Section: Discussionmentioning
confidence: 99%
“…This finding rules out the possibility that the US controls sleep, e.g., making the animals more aroused by feeding them the afternoon before the following night. An appetitive stimulus such as sucrose is known to activate octopaminergic neurons of the ventral unpaired median (VUM) neurons of the subesophageal ganglion (Schroter et al 2007), and the activity of one of these neurons, the VUMmx1, was found to provide a sufficient reinforcing signal in odor conditioning (Hammer and Menzel 1998). Injection of octopamine (OA) systemically or into the antennal lobe or the mushroom body arouses the animal, leads to more sucrose uptake (Bicker and Menzel 1989), and can act as a substitute for the US if injected locally into the antennal lobe or the mushroom body calyces shortly after an odor CS (Hammer and Menzel 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although gustatory receptor neurons tuned to sucrose have been located within specialized sensilla on the antennae, mouth parts, and tarsi (Whitehead and Larsen 1976;Whitehead 1978;Haupt 2004;de Brito Sanchez et al 2005de Brito Sanchez 2011), little is known about the neural circuits allowing these receptor neurons to convey US information to the central level and, more specifically, to VUM mx1 . This circuit is probably localized in the subesophageal ganglion, which is the first synaptic relay in the gustatory pathway (Altman and Kien 1987;Schröter et al 2006). Similarly, CS processing has been studied in terms of the processing from olfactory receptors to the mushroom bodies, yet little is known about the possible recoding of sensory input by mushroom bodies based on their experienced value.…”
Section: Cs Variationsmentioning
confidence: 99%